Instant wealth, wake up rich! : discover the secret of the new entrepreneurial mind - Howard, Christopher, 1970- (Wiley, 2010)
"The power to create great wealth is already within you. But monetizing that raw energy doesn't happen by itself. As Christopher Howard shows, building great wealth is a dual process. It begins by identifying your passion--the things you truly and deeply care about, whatever they may be. Next, passion needs to be endowed with purpose: a clearly defined vision of the future you intend to create. As a true entrepreneur himself, Christopher Howard has put these lessons to work in the creation of his own fast-growing international business. What's worked for him--and for so many other hugely successful entrepreneurs--can work for you too. All it takes is passion, purpose, and waking up to instant wealth"--Resource description page